The power of light: Impact on the performance of biocontrol agents under minimal nutrient conditions - Karlsson, Maria E.; Hellström, Maria; Flöhr, Adam; Bergstrand, Karl-Johan; Alsanius, Beatrix W. (Frontiers in Microbiology, 2023)
Background: The spectral distribution of light (light quality) has recently been identified as an important factor in the dynamics and function of leaf-associated microbes. This study investigated the impact of light quality on three commercial biocontrol agents (BCA): Bacillus amyloliquefaciens (BA), Pseudomonas chlororaphis (PC), and Streptomyces griseoviridis (SG). Methods: The impact of light exposure on sole carbon source utilization, biofilm formation, and biosurfactant production by the selected BCA was studied using phenotypic microarray (PM) including 190 sole carbon sources (OmniLog®, PM panels 1 and 2). The BCA were exposed to five monochromatic light conditions (420, 460, 530, 630, and 660 nm) and darkness during incubation, at an intensity of 50 µmol m-2 s-1. Results: Light exposure together with specific carbon source increased respiration in all three BCA. Light quality influenced sole carbon utilization for the different BCA, with BA and PC showing increased respiration when exposed to wavelengths within the blue spectrum (420 nm, 460 nm) while respiration of selected carbon sources by SG increased in the presence of red light (630 nm, 660 nm). Only one carbon source (capric acid) generated biosurfactant production in all three BCA. A combination of light quality and sole carbon source increased biofilm formation in all three BCA. BA showed significantly higher biofilm formation when exposed to blue (460 nm) and green (530 nm) light and propagated in D-sucrose, D-fructose, and dulcitol. PC showed higher biofilm formation when exposed to blue light. Biofilm formation by SG increased when exposed to red light (630 nm) and propagated in citraconic acid. Conclusion: To increase attachment and success in BCA introduced into the phyllosphere, a suitable combination of light quality and nutrient conditions could be used.